Answer:
(2, -1, -4).
Explanation:
-5x - 4y + 6z = -30
4x + 4y + 2z = -4
-3x - 4y +z = -6
Adding the first and second equation eliminates y:
-x + 8z = -34
Adding the second and third equation eliminates y:
x + 3z = -10
Adding theses last 2 equations eliminates x:
11z = -44
z = -4.
Substitute for z in the last equation:
x + 3(-4) = -10
x = -10 + 12 = 2.
Finally substituting for x and z in the first equation in the question:
-5(2) - 4y + 6(-4) = -30
-10 - 4y - 24 = -30
-4y = -30 + 24 + 10 = 4
y = -1.